2006
DOI: 10.1007/s00421-006-0244-3
|View full text |Cite
|
Sign up to set email alerts
|

Deficit in human muscle strength with cast immobilization: contribution of inorganic phosphate

Abstract: Metabolic factors have been proposed to explain strength deficits observed in skeletal muscle with immobilization that are not completely accounted for by changes in muscle cross-sectional area (CSA) and neural adaptations. The aim of this study was to quantify changes in the resting inorganic phosphate (Pi) concentration from the medial gastrocnemius muscle during immobilization, reloading and rehabilitation. Additionally, we assessed the contributions of CSA, muscle activation and Pi concentration to plantar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
4
10
1
2
Order By: Relevance
“…While exercise causes fatigue (Westerblad and Allen 2002), immobilization leads to weakness of the tissue (Christensen et al 2008;Berg and Tesch 1996;Pathare et al 2006). Fatigue has been deWned as any exerciseinduced reduction in the maximal power capacity to generate force or power output (Vollestad 1997), whereas weakness describes a maintained low maximal force, which persists over longer periods and appears independent of exercise (Vollestad 1997).…”
Section: Discussionmentioning
confidence: 99%
“…While exercise causes fatigue (Westerblad and Allen 2002), immobilization leads to weakness of the tissue (Christensen et al 2008;Berg and Tesch 1996;Pathare et al 2006). Fatigue has been deWned as any exerciseinduced reduction in the maximal power capacity to generate force or power output (Vollestad 1997), whereas weakness describes a maintained low maximal force, which persists over longer periods and appears independent of exercise (Vollestad 1997).…”
Section: Discussionmentioning
confidence: 99%
“…They attributed their results to changes in the ability of calcium release from the sarcoplasmic reticulum or to a reduction in the number of cross-bridges, or to some change in the contractile apparatus that might be compatible with the absence of changes in the EMG signals. An attempt to explain this reduction in muscle strength was made by Pathare et al 35 , who found increased levels of inorganic phosphate in the muscle after immobilization, which would inhibit muscle contraction by preventing the connection of the myosin heads with the actin filaments. However, they do not explain how this increase in muscle inorganic phosphate is responsible for the inhibition of the contractile apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Given the large abundance of water in the human body, clinical MRI typically utilizes the hydrogen nuclei (also known as protons) in free and macromolecular-bound water. Sodium and phosphorus are also of interest in musculoskeletal imaging and can be used to noninvasively quantify total sodium changes during exercise and disease states, 9 examine muscle metabolism during exercise or disuse, 26,27,29 and monitor pH, 22 among other applications. However, these nuclei are less abundant and need larger field strengths (3.0-7.0 T) to have a sufficient signal-to-noise ratio before strong and meaningful clinical conclusions can be made.…”
Section: T T Synopsismentioning
confidence: 99%
“…The ability to monitor in vivo spectral changes has a range of clinical applications for the musculoskeletal system, including monitoring intracellular and extracellular fat changes, 31 exercise-induced changes in metabolites, 14 intracellular pH abnormalities in chronic fatigue syndrome, 22 and examining muscular response to neurological insult and/or disuse through intramyocellular lipid content 33 or changes in inorganic phosphate. 26,27 SPATIAL ENCODING I n addition to chemical information, the signal can be encoded with spatial position and used to obtain an image. This is done by applying additional magnetic field gradients with a predictable change in field strength along a particular axis.…”
Section: Key Pointsmentioning
confidence: 99%